Applying of Design of Experiments (DOE) Methodology to Improve the Quality of Processed Cake (Journal of Hama University, 2022)
The purpose of this research is to improve the quality of a sponge cake manufactured by batches method in rotary ovens. The characteristics to be improved in the processed cake were determined by the moisture, water activity, appearance and degree of baking. Appearance and degree of baking were evaluated by tasters, and moisture and water activity were measured by appropriate objective methods. For this purpose, an experimental plan had been developed using the method of designing complete factor experiments with four factors and two levels, by using the Statgraphic plus statistical program. Factors included the amount of sugar, amount of flour, baking temperature, and baking time. With this methodology, the study provided important information and clear results for the effect of each factor on each of the studied characteristics, and it enabled us to find the mathematical relationship of those factors on the studied characteristics at all values in the studied field with the values of acceptable regression coefficients.